Impoliteness of Directive Speech Acts in Online Indonesian Language Learning - Rahmawati, Laili Etika; Hidayat, Nurul; Kurniawan, Andra (Journal of Pragmatics Research, 2021)
This study aims to describe the impoliteness of directive speech acts in online Indonesian language learning. The data collection technique in this study used the observation, note, and record technique. The object of this research was the analysis of directive speech act impoliteness. The data analysis technique used in this study was a data triangulation model. The study results indicate an impoliteness of directive speech acts on Indonesian language learning conducted by the teacher. The teacher unintentionally performed impoliteness on the directive speech acts. The first data found that the teacher asked all the students to pay attention impolitely. The second data showed that the teacher as a speaker prohibits students from taking attendance. The third data showed that the teacher used the impolite directive speech acts when saying the utter "unnecessary" and "you pay less attention" to the students who forgot to attend the class. The data (3a) above includes the impoliteness of the directive speech act of the requesting because it does not contain politeness elements that can smooth speech. Data (4a) The teacher asks students who are not members to leave the WhatsApp group, but the teacher does not use soft sentences. Data (5a) stated that the teacher instructs the students to cut the paper using a cutter and make lines on it . Next, the data (5b) stated the teacher asks students to look at the learning material using impoliteness directive speech acts. Data (5c) stated that the teacher instructs students not to forget to fill the attendance. Data (6a) stated the teacher asks students to join the google classroom but does not use polite sentences. The data includes the directive speech act of the requesting marked with the word beg. Data (7a) Teachers require students to have sufficient quotas when participating in learning Indonesian online. Keywords: impoliteness, directive speech acts, Online learning